Design of Thermoelectric-Based Salinity and Temperature Control for Nomei Fish - Prasetia, Abdul Muis; Sartika, Linda; Setiyawan, Muhammad Dicky; Salim, Gazali (DPTE FT UNY, 2024)
Nomei fish (Harpodon nehereus) are creatures commonly found under layers of mud or fine sand along the coast. They cannot survive in waters with extreme salinity and temperature. When daylight comes and the air temperature rises, the temperature inside the fishpond also tends to rise, while when night falls, the water in the pond becomes colder. Extreme temperature changes, both high and low, can make these fish susceptible to disease and impact their ability to feed and immune system. This research is developmental research as the objective is to test the control of salinity and temperature in Nomei fishponds. To achieve this goal, a system has been developed. The system uses two sensors, namely a conductivity sensor that serves to measure the level of water salinity and sends data to the Arduino device to set the pump based on an average of about 17 ppm. In addition, there is also a temperature sensor that measures the water temperature in the pool and sends data to the Arduino device to adjust the heater and thermoelectric based on the average temperature between 28.5°C and 31.5°C, to maintain stable water quality. The results of this study show that the developed system successfully maintains and controls the salinity and temperature in the Nomei fishpond in accordance with the predetermined set points.